2008
DOI: 10.1038/sj.bjc.6604364
|View full text |Cite
|
Sign up to set email alerts
|

MUC4 and MUC5AC are highly specific tumour-associated mucins in biliary tract cancer

Abstract: Alterations in epithelial mucin expression are associated with carcinogenesis, but there are few data in biliary tract cancer (BTC). In pancreatic malignancy, MUC4 is a diagnostic and prognostic tumour marker, whereas MUC5AC has been proposed as a sensitive serological marker for BTC. We assessed MUC4 and MUC5AC expression in (i) prospectively collected bile and serum specimens from 72 patients with biliary obstruction (39 BTC) by real-time reverse transcriptase -PCR (qPCR) and western blot analysis, and (ii) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…Intensity of staining was reported by a histopathologist using a widely used semi quantitative scoring system (0; no staining, +; weak, ++; moderate and +++; strongly positive staining) [18]. The number of biliary epithelial cells stained positive were also scored (0; <5%, +; 5%–20%, ++; 20%–50% and +++; >50% stained positive [12]. Comparison of results was performed for both number of cells positively stained and intensity of staining.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensity of staining was reported by a histopathologist using a widely used semi quantitative scoring system (0; no staining, +; weak, ++; moderate and +++; strongly positive staining) [18]. The number of biliary epithelial cells stained positive were also scored (0; <5%, +; 5%–20%, ++; 20%–50% and +++; >50% stained positive [12]. Comparison of results was performed for both number of cells positively stained and intensity of staining.…”
Section: Methodsmentioning
confidence: 99%
“…A potential confounding factor in biliary samples is leukocyte RNA contamination as a result of biliary infection, particularly in those with biliary obstruction. Previous work has shown that RNA from bile and/or biliary brushings can be useful for qPCR when measuring small numbers of highly expressed genes [12–13]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, sandwich ELISA of serum MUC5AC seems to be promising and provides clinical value for diagnosis and prognosis of CCA. MUC4 and MUC5AC were also investigated by Matull et al [19 ] using real-time reverse transcriptase-PCR (qPCR) and Western blot in serum and bile samples prospectively collected from 72 patients with biliary obstruction of different causes, including 39 CCA and seven PSC. Serum MUC5AC protein was detected in 17 out of 39 (44%) CCA but not in the other malignancies.…”
Section: Serum Tumour Markersmentioning
confidence: 99%
“…26,28 The gel-forming mucin MUC5ac is a marker for biliary tract cancer. 29 Findings show that MUC 3, 4, and 5ac are overexpressed in ampullary malignancies and that MUC3 is an independent predictor of poor survival. 30 The expression of mucins differs between tumors with pancreaticobiliary and intestinal differentiation.…”
Section: Proteins Growth Factors and Receptorsmentioning
confidence: 96%